Oxidative stress status and neuroprotection of tocotrienols in chronic cerebral hypoperfusion-induced neurodegeneration rat animal model - Mohamed, Wael Mohamed Yousef; Sayeed, Sayyada; Saxena, Anil Kumar; Syed Ahmad, Pakeer Oothuman (Wolters Kluwer - Medknow, 2018)
Background: Reduced cerebral blood flow is associated with aging, neurodegenerative disorders, and an increased formation of reactive oxygen species. This study was designed to assess the potential use of vitamin E as an antioxidant and neuroprotective agent using 2-vessel occlusion (2VO) rat animal model. Materials and Methods: Twenty-four Sprague Dawley rats weighing 200–250 g were equally divided into the following three groups: SHAM control, 2VO, and 2VO+E (treated daily with vitamin E tocotrienol, 100 mg/kg, orally following 2VO). On the 8th week after 2VO surgery, rats were euthanized and the hippocampi were isolated with the estimation of viable neuronal cell count in the hippocampal CA-1 region. The isoprostane F2 (Iso-F2) levels were also measured in the brain homogenates to quantify the oxidative stress levels. Results: There was significantly higher neuronal cell death in the hippocampal CA-1 region and increased Iso-F2 levels in the 2VO group compared to the SHAM control group (P < 0.05). Conversely, no significant difference was observed with regard to the neuronal cell death and Iso-F2 levels in the 2VO+E group and the SHAM control group (P > 0.05). Conclusion: This study demonstrates the effectiveness of vitamin E tocotrienol as a neuroprotective and antioxidant agent in chronic cerebral hypoperfusion-induced neurodegeneration in rats.